Improvement of Workability and Integrity for Ambient Ground Rubber as Elastomer Alternative: Direct Incorporation and Functionalization - Rakhman, Moshe Z (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The main barriers to the wide use of ambient ground tire rubber (GTR) are the absence of breakdown in shear mixing, lack of compatibility, and co-curing with the polymer matrix. The functionalization of the GTR was realized through dispersive shear-induced mixing, with the disintegration of the aggregates due to the swelling gradient, oxidation of a network and to sequence order. The GTR-functionalized macro-composite comprised a co-cured compatible GTR and an unsaturated elastomer at any ratio, retaining the excellent initial properties, unlike a depolymerized reclaim. This blend had an unexpected integrity effect: the enhanced workability of the roll-processed, self-sustained web with regular surface skin topography and verified integrity for an uncured blend. Functionalization appears to be a more significant factor than GTR size, characterized by lower gel content, improved abrasion, and tear resistance compared to the virgin elastomer blend. Workability and integrity control indicators were selected